HUBUNGAN ANTARA TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG DISMINORE DENGAN KESIAPAN MENGHADAPI DISMINORE DI RW 03 KELURAHAN KALIJATEN KECAMATAN TAMAN SIDOARJO TAHUN 2021 - Ardiyanti Hidayah; Najah Soraya Niah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2022)
Introduction :Dysminore is painful during menstruation, usually with a sense of cramps and concentrated in the lower abdomen. This research aims to Analyze the relationship between the level of knowledge of young women about disminore with readiness to face disminore in the Kalijaten sub-district, Taman Kecamatan Sidoarjo regency Methode: Observational Analytic Design, cross sectional approach of population 54 young adolescent girls early teens middle adolescents late teens, Simple Random Sampling sample technique, a sample of 48 teenage data collection by Questionnaire, coding data processing, scoring, tabulating and analyzed by chi square test Result: Results of research on adolescent girls The majority of teenagers' knowledge is sufficient, namely 21 people (83.3%), most of the girls who will face disminore who have preparedness are 37 people (77.1%). Statistical testing with chi square test obtained p value α α with p = 0.000. shows there is a relationship between the level of knowledge of young women with readiness to face disminore in Rw 03 Kalijaten Village Taman District Sidoarjo Regency. Discussion : From the results of the analysis it is expected for medical personnel to provide counseling and education for adolescents to be ready to face disminore and accept that disminore is something physiological to a woman.